Assessment of symbiont-targeted control on non-target stink bugs and their associated egg parasitoids: Could this technique be suitable against Halyomorpha halys in New Zealand? - Sofia V. Prieto; Gonzalo A. Avila; Barbara Lima; Elena Gonella; Alberto Alma (Journal of Pest Science, 2025)
The potential arrival of Halyomorpha halys in New Zealand jeopardizes a vast range of crops. Therefore, different preparedness strategies are being assessed before its arrival. A symbiont-targeted control strategy might be used along with other control tactics such as biological control. Prior its implementation, it is necessary to assess its potential impact on non-target stink bug species and their associated egg parasitoids. In this study, the effect of symbiont-targeted control was evaluated on three stink bug species in New Zealand, Oechalia schellenbergii (a native predatory species), Nezara viridula (a cosmopolitan pest) and Monteithiella humeralis (a non-pest adventive species). The interference of anti-symbiont treatment of egg masses with their associated Trissolcus egg parasitoids, namely T. basalis and T. oenone , was also tested. A variable response to symbiont elimination was observed in stink bug species, with N. viridula and M. humeralis undergoing high mortality and no negative effect detected for O. schellenbergii . Parasitism of N. viridula by T. basalis declined on egg masses treated with an anti-symbiont biocomplex or water. Similar results were obtained for T. oenone parasitizing eggs of M. humeralis ; while, a parasitism increase was observed for O. schellenbergii egg masses exposed to anti-symbiont treatment and treated with water. These results confirm previous evidence of species-specific response to anti-symbiont control and indicate a moderate and variable effect on egg parasitism. Such responses suggest that symbiont-targeted control would not significantly interfere with the native insect communities that may interact with H. halys , encouraging the future incorporation of symbiont-targeted control in pest management programs.